1991
DOI: 10.1063/1.348614
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenation of R2Fe17 compounds: R=rare earth

Abstract: Magnetic properties of a new family of ternary rareearth iron nitrides R2Fe17N3−δ (invited)The reaction between nitrogen gas and the series of R, Fe,, intermetallic compounds is studied by thermopiezic analysis on micron-size powders. Nitrogen diffusion in the range 300-550 "C can be represented by an activated interstitial diffusion process D = Doe-Em'kT with Do = 1.95 X 10 -lo m2 s -' and an activation energy E,,, = 0.8 1 eV. This stage of the nitrogenation reaction leads to the formation of R, Fe,, N, _ 6 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(17 citation statements)
references
References 8 publications
0
13
0
4
Order By: Relevance
“…Both T N and Y T are below room temperature and thus too low from an applications perspective. Correspondingly, considerable effort has been spent in attempting to increase Y T /Tc for this series, and such studies have shown that the partial substitution of Fe by nonmagnetic elements such as Si, Al and Ga [3,4], or the absorption of H, N or C into interstitial sites, increases the onset of ferromagnetism in such R 2 Fe 17 compounds significantly [5][6][7]. In contrast, the substitution of Mn -a magnetic species -for Fe produces a complicated behavior, with ferromagnetism being suppressed initially [8].…”
Section: Introductionmentioning
confidence: 98%
“…Both T N and Y T are below room temperature and thus too low from an applications perspective. Correspondingly, considerable effort has been spent in attempting to increase Y T /Tc for this series, and such studies have shown that the partial substitution of Fe by nonmagnetic elements such as Si, Al and Ga [3,4], or the absorption of H, N or C into interstitial sites, increases the onset of ferromagnetism in such R 2 Fe 17 compounds significantly [5][6][7]. In contrast, the substitution of Mn -a magnetic species -for Fe produces a complicated behavior, with ferromagnetism being suppressed initially [8].…”
Section: Introductionmentioning
confidence: 98%
“…Sm 2 Fe 17 N 3 is another strong permanent magnet compound. Although it has a problem for thermodynamic instability at high temperatures [2], the magnetization, 1.54 T, is slightly smaller but comparable, and the uniaxial anisotropy, 140 kOe [3] at room temperature, is stronger than that of Nd 2 Fe 14 B.…”
Section: Introductionmentioning
confidence: 99%
“…Both materials begin to absorb nitrogen at nearly the same temperature, but the maximum pressure drop temperature of the intact strips is observed at about 620 • C significantly higher than that (560 • C) of the crushed strips, due to the fact that the reaction interface area between nitrogen and particles in the intact strips is significantly less than that in the case of the crushed strips. Increasing nitrogenation temperature may help the intact strips to achieve nitrogen saturation in a reasonable time by increasing the nitrogen diffusion rate [10]. Fig.…”
Section: Resultsmentioning
confidence: 99%